Dialysis Service in the Embattled Tigray Region of Ethiopia: A Call to Action. (24th June 2022) - Berhe, Ephrem; Ross, Will; Teka, Hale; Abraha, Hiluf Ebuy; Wall, Lewis
Abstract : Haemodialysis is extremely limited in low-income countries. Access to haemodialysis is further curtailed in areas of active conflict and political instability. Haemodialysis in the Tigray region of Ethiopia has been dramatically affected by the ongoing civil war. Rapid assessment from the data available at Ayder Hospital's haemodialysis unit registry, 2015–2021, shows that enrollment of patients in the haemodialysis service has plummeted since the war broke out. Patient flow has decreased by 37.3% from the previous yearly average. This is in contrary to the assumption that enrollment would increase because patients could not travel to haemodialysis services in the rest of the country due to the complete blockade. Compared to the prewar period, the mortality rate has doubled in the first year after the war broke out, i.e., 28 deaths out of 110 haemodialysis recipients in 2020 vs. 43 deaths out of 81 haemodialysis recipients in the year 2021. These untoward outcomes reflect the persistent interruption of haemodialysis supplies, lack of transportation to the hospital, lack of financial resources, and the unavailability of basic medications due to the war and the ongoing economic and humanitarian blockade of Tigray in Northern Ethiopia. In the setting of this medical catastrophe, the international community should mobilize to advocate for resumption of life-saving haemodialysis treatment in Ethiopia's Tigray region and put pressure on the Ethiopian government to allow the passage of life-saving medicines, essential medical equipment, and consumables for haemodialysis into Tigray.